Building community prosperity through scaling out WLE/ICRISAT agricultural water management interventions for sustainable crop intensification in Central India - CGIAR Research Program on Water, Land and Ecosystems (2019)
Water harvesting and productivity interventions implemented by WLE/ICRISAT and the Central Agroforestry Research Institute on a pilot watershed in central India had significant impacts on water resources, incomes and farmers' livelihoods. As a result, the Government of Uttar Pradesh has asked ICRISAT and a consortium of national partners to scale the model out to over 35,000 ha.